Fabrication and characterization of conductive poly (3,4-ethylenedioxythiophene) doped with hyaluronic acid/poly (L-lactic acid) composite film for biomedical application - Wang, S; Guan, S; Wang, J; Liu, H; Liu, T; Ma, X; Cui, Z (Elsevier, 2016)
Poly 3,4-ethylenedioxythiophene (PEDOT), a polythiophene derivative, has been proved to be modified by chemical process as biocompatible conductive polymer for biomedical applications. In this study, novel hyaluronic acid (HA)-doped PEDOT nanoparticles were synthesized by the method of chemical oxidative polymerization, then conductive PEDOT-HA/poly(l-lactic acid) (PLLA) composite films were prepared. The physicochemical characteristics and biocompatibility of films were further investigated. FTIR, Raman and EDX analysis demonstrated that HA was successfully doped into PEDOT particles. Cyclic voltammograms indicated PEDOT-HA particles had favorable electrochemical stability. PEDOT-HA/PLLA films showed lower surface contact angle and faster degradation degree compared with PLLA films. Moreover, the cytotoxicity test of PEDOT-HA/PLLA films showed that neuron-like pheochromocytoma (PC12) cells adhered and spread well on the surface of PEDOT-HA/PLLA films and cell viability denoted by MTT assay had a significant increase. PEDOT-HA/PLLA films modified with laminin (LN) also exhibited an efficiently elongated cell morphology observed by fluorescent microscope and metallographic microscope. Furthermore, PEDOT-HA/PLLA films were subjected to different current intensity to elucidate the effect of electrical stimulation (ES) on neurite outgrowth of PC12 cells. ES (0.5 mA, 2 h) significantly promoted neurite outgrowth with an average value length of 122 ± 5 μm and enhanced the mRNA expression of growth-associated protein (GAP43) and synaptophysin (SYP) in PC12 cells when compared with other ES groups. These results suggest that PEDOT-HA/PLLA film combined with ES are conducive to cell growth and neurite outgrowth, indicating the conductive PEDOT-HA/PLLA film may be an attractive candidate with ES for enhancing nerve regeneration in nerve tissue engineering.